2006
DOI: 10.1097/01.tp.0000226234.76036.c1
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lactic Acidosis in the Graft During Organ Harvest, Cold Storage, and Reperfusion of Human Liver Allografts Predicts Subsequent Ischemia Reperfusion Injury

Abstract: Interstitial lactic acidosis in the donor allograft is associated with significant reperfusion injury on implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 22 publications
4
26
0
1
Order By: Relevance
“…These findings are in agreement with both of our previous studies on total warm liver ischemia as well as studies done by other research groups [17,25,26] . Lactate levels in the normally perfused part of the liver were not affected by occlusion of another part of the liver, i.e.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are in agreement with both of our previous studies on total warm liver ischemia as well as studies done by other research groups [17,25,26] . Lactate levels in the normally perfused part of the liver were not affected by occlusion of another part of the liver, i.e.…”
Section: Discussionsupporting
confidence: 83%
“…Metabolic substances (lactate, pyruvate, glucose, glycerol, urea, and glutamate) and mediators of inflammation (cytokines, chemokines, and complement activation products) could be sampled from the intercellular space in hepatic tissue by this method. In liver transplantation, high concentrations of intrahepatic lactate before reperfusion correlated with the magnitude of reperfusion injury . Poorly functioning liver grafts were associated with high lactate concentrations prior to reperfusion and complement activation as seen by C4d deposition detected by histological examination .…”
Section: Liver Transplantationmentioning
confidence: 96%
“…Microdialysis catheters are able to sample metabolic substances and inflammatory mediators directly from the organ of interest. We have found that ischemia can be detected as increased lactate levels and lactate/pyruvate ratios and that rejection can be detected as increased lactate and pyruvate levels with stable lactate/pyruvate ratios .…”
mentioning
confidence: 99%